Children Exposed to Interparental Violence: A Study of Portuguese Children from 7-9 Years of Age - Telma Catarina Almeida (Suma Psicológica, 2022)
Introduction: Exposure to interparental violence is a type of child maltreatment linked to a higher risk of physical and mental health problems. This research considers the experiences of young Portuguese children exposed to interparental violence. The goal is to explore the associations between interparental conflict in children, their perceptions of conflict properties, threat, self-blame, and the relationship with their parents. Method: The research protocol was applied to 888 Portuguese children between 7 and 9 years of age, of whom 123 are victims of interparental violence. Results: The results showed that witnessing interparental conflict is positively correlated with children’s self-blame and insight into conflict properties and negatively correlated with children’s insight into the parent-child relationship. Conclusion: These results provide strong support for the hypothesis that witnessing interparental conflict is associated with adverse outcomes in young children. Findings highlight the importance of identifying children exposed.